Effect of Phosphorus Fertilization on Dry matter Accumulation and it's Remobilization in Oil seed Flax (Linum usitatissimum L.) under rainfed condition - Mohamed, Shiren Jalal; Ahmed, Shilan Mahmood; Mahmood, Solaf Adnan (Sulaimani Journal for Pure and Applied Sciences, 2019)
This experiment was carried at Qlyasan Research Station. Faculty of Agricultural Sciences, University of Sulaimani, during 2016-2017 to study the effect of four levels of phosphorus fertilizer in the form of P2O5 (0 control, 100, 200 and 300 kg P2O5ha-1) on two oilseed flax varieties (Poland and Syria local) dry matter and Phosphor accumulation and their translocation from source to sink . Results showed that Poland variety with the 200kg P2o5 ha-1 in all studied parameters significantly being higher than Syria local, and other levels of P2O5 fertilizer. Compared to control 200kg P2O5 increased DM accumulation at 50% anthesis by (44.48 and 27.04%), DM translocation efficiency by (24.46and 38.19 %), Contribution of leaves DM to final grain by (53.57 and 44.060%), P accumulation in vegetative tissues at 50% anthesis by (69.59 and 81.65 %), P translocation efficiency by (51.85 and 70.02%), leaf P contribution to final grain by (50.69 and 73.63%), also at maturity increased biological yield by (27.16 and 29.72%), and increased grain yield by (20 and 27%) for Poland and Syria local respectively, with no significant increment above that level. In both varieties at 50% anthesis the leaves DM were increased and reached peak at 200kg P2O5ha-1 but as the plant reached maturity the leaves DM significantly lower by ten times than stem DM+NG. These results suggest that 1.The leaves in oil seed flax are the major DM and P contributor to grain after anthesis whereas the stem and NG are the stronger demand for DM and P post anthesis.2. Variety of Poland under the 200kgP2O5 ha-1 could be suitable for grain yield under rainfed condition in Sulaimani province.
Keywords: Flax variety; Phosphorus fertilizer; Dry matter accumulation; P remobilization